2016
DOI: 10.5041/rmmj.10247
|View full text |Cite
|
Sign up to set email alerts
|

For Better Orchiopexy, Processus Vaginalis Should Be Dissected and a High Ligation Should Be Performed

Abstract: ObjectiveData on the prevalence of patent processus vaginalis (PPV) and hernia in patients with cryptorchidism are controversial. While some pediatric surgeons do not dissect the processus vaginalis (PV), most prefer to do so to prevent hernia formation and to achieve an effective orchiopexy outcome. This study was performed to evaluate the importance of dissection and high ligation of the PV during treatment of undescended testis (UT).MethodsThe clinical findings and surgical procedures of 55 patients with UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However when the testis is in a higher position, such as in the inguinal canal or just at the external ring, TSO brings troublesome complications include injury to the vas deferens and testicular vessels. In 2016, Lopes et al published articles about post-operation complications ( 15 , 16 ). Hernia, hydrocele, testicle ascending and atrophy happens, owing to insufficient (retroperitoneal) mobilization of vas and vessels and/or inadequate high ligation of patent processus vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…However when the testis is in a higher position, such as in the inguinal canal or just at the external ring, TSO brings troublesome complications include injury to the vas deferens and testicular vessels. In 2016, Lopes et al published articles about post-operation complications ( 15 , 16 ). Hernia, hydrocele, testicle ascending and atrophy happens, owing to insufficient (retroperitoneal) mobilization of vas and vessels and/or inadequate high ligation of patent processus vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the controversy over the management of PPV during surgical exploration persists. 21 , 22 It remains for the surgeon to decide whether it is worthwhile to prevent a metachronous hernia with a probability of approximately 6%. 23 Finally, low birth weight and preterm birth, which were closely associated with cryptorchidism and PPV, were not analyzed in this study because the number of patients with low birth weight or preterm birth was too small to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect inguinal hernia is common in the pediatric age group. It is often congenital and arises from a patent processus vaginalis, a peritoneal channel that has failed to close and is also found in up to 90% of undescended testes (1)(2)(3). Although some surgeons suggested the nonligation of the processus vaginalis in the context of a indirect hernia and orchidopexy, their findings were based on limited evidence to be interpreted with suspicion (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…High ligation was considered as essential to avoid recurrence of indirect inguinal hernia and is also the standard part of inguinal orchiopexy for patent processus vaginalis (1,(6)(7)(8). Sonmez et al demonstrated the importance of dissection and high ligation of processus vaginalis to prevent hernia formation and provide a tension-free orchidopexy procedure (2).…”
Section: Discussionmentioning
confidence: 99%